Advances in CO₂ utilization technology: A patent landscape review. (July 2018) - Norhasyima, R.S.; Mahlia, T.M.I.
Highlights: Current patent review on CO2 utilization technologies for CCUS application using Derwent Innovation platform. Emerging hybrid technologies concepts with disruptive potential was found and potential future study proposed. Health, safety and environmental impact due to CO2 utilization technologies implementation. Abstract: There is rising concern on the increasing trend of global warming due to anthropogenic CO₂ emission which steers progress of carbon capture and storage (CCS) projects worldwide. However, due to high cost and uncertainties in long term geological storage, there is a growing inclination to include utilization, which re-use the CO2, hence carbon capture utilization and storage (CCUS). Additionally, it is expected to generate income to offset the initial costs. This study methodically review patents on CO₂ utilization technologies for CCUS application published between year 1980–2017. It was conducted using the Derwent Innovation patent database and more than 3000 number of patents was identified. The patents identified are in the field of enhanced oil recovery (EOR) and enhanced coal-bed methane (ECBM), chemical and fuel, mineral carbonation, biological algae cultivation and enhanced geothermal system (EGS). Over 60% of these patents were published since the last 10 years, and a sharp increase in patents were seen in the last 5 years (∼38%). The top major patent types are patents granted in the United States (US), China (CN) and Canada (CA) which makes of 3/5 of the overall patent type found. Recent patents published include enhancements to the state-of-the-art technologies and hybrid concepts such as in photo-bioreactor in algae cultivation, chemical reaction and EGS. From this study, it was found that further research for the best CO₂ utilization method which fulfil the need of an economic, safe, non-location dependent and environmentally friendly whilst efficiently mitigate the worldwide global warming issue is much needed.